(3GdeMGSHI aj eLGd GdJfejI GdeSJOGeI Hjf GdfXQjI hGdJWHjb (B/s - (3HOhj, eMeO YHGSs; (3GdHdJGLj, jSQi eMeO s ((3GdEScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2013)
(3GdeMGSHI Yf GdJfejI GdeSJOGeI ef efXhQ GdeMGSHI GdeGdjI(B- (3GdEWGQ GdeaGgjej ddJfejI GdeSJOGeI(B- (3GYJHGQGJ GdbjGS aj eLGd GdeMGSHI Yf GdJfejI GdeSJOGeI(B- (3GYJHGQGJ GdEaUGM aj eLGd GdeMGSHI Yf GdJfejI GdeSJOGeI(B- (3GdeMGSHI Yf GdJfejI GdeSJOGeI ef efXhQ eMGSHI GdJcGdja(B- (3bjGS GdJcGdja GdHjFjI(B- (3JNUjU GdJcGdja GdHjFjI HESJNOGe CSdhH GdJcGdja Ydi CSGS GdfTGW(B- (3GdfehPL GdeJcGed dYedjI bjGS hJNUjU GdJcGdja GdHjFjI Ydi GdefJLGJ(B- (3MGdGJ JWHjbjI ddeMGSHI Yf GdJfejI GdeSJOGeIs
(3GdeQGLY U(B.381s
Keywords: (3GbJUGOjGJ GdJfejIs; (3GdJfejI GdEbJUGOjIs; (3GdeMGSHIs